Bioinformatic characterization and gene expression pattern of apoptosis inhibitor from Macrobrachium rosenbergii challenged with infectious hypodermal and hematopoietic necrosis virus - Arockiaraj, J.; Vanaraja, P.; Easwvaran, S.; Singh, A.; Othman, R.Y.; Bhassu, S. (2011)
Apoptosis is genetically programmed cellular killing processes that execute unnecessary or infected cells. It plays an important role in embryogenesis, homeostasis, insect metamorphosis and immunity. Apoptosis inhibitor (MrIAP) was sequenced from the freshwater giant prawn Macrobrachium rosenbergii using Illumina Solexa Genome Analyzer Technique. MrIAP consisted of 1753 base pair nucleotides encoded 535 polypeptide with an estimated molecular mass of 60 kDa. MrIAP amino acid sequence contains IAP superfamily domain between 5 and 490. The deduced amino acid sequences of the MrIAP were aligned with the other IAP family members. The highest sequence similarity was observed in IAP-5 from ant Camponotus floridanus (67%) followed by IAP from body louse Pediculus humanus corporis (66%) and the lowest (62%) in IAP-5 isoform-5 from common chimpanzee Pan troglodytes and IAP-5 from Aedes aegypti. The IAP phylogenetic tree showed that MrIAP closely related to other arthropod blacklegged tick Ixodes scapularis, formed a sister group with IAP from a hemichordate acorn worm Saccoglossus kowalevskii and finally clustered together with IAPs from fish groups. The quantitative real time PCR analysis revealed that significantly (P < 0.05) highest expression was noticed in hepatopancreas and significantly (P < 0.05) lowest expression in pleopods. Based on the results of gene expression analysis, MrIAP mRNA transcription in M. rosenbergii challenged to infectious hypodermal and hematopoietic necrosis virus (IHHNV) was highly induced in hepatopancreas. The collective results of this study indicate that the MrIAP is an essential immune gene and influences the immune response against IHHNV infection in M. rosenbergii. (C) 2011 Elsevier Ltd. All rights reserved.